Bronchopulmonary infection with Pseudomonas aeruginosa in patients infected with human immunodeficiency virus. Issue 2 (April 1995) - Ali, N J; Kessel, D; Miller, R F
Abstract : BACKGROUND–Pseudomonas aeruginosa infection is uncommon in HIV infected patients and is usually nosocomially acquired and associated with risk factors such as neutropenia or central lines. We have recently noted an increase in the number of respiratory isolates of Ps aeruginosa in hospitalised HIV positive patients and sought to describe the clinical correlates of this observation. METHODS–A retrospective case notes review of HIV positive patients admitted to a specialist unit for respiratory investigations from January 1989 to December 1993 was undertaken in order to identify those with Ps aeruginosa respiratory infection and to describe associated risk factors, patterns of presentation and radiographic abnormalities. RESULTS–Of 617 patients admitted 38 (6%) had Ps aeruginosa respiratory infection (notes were incomplete in 1 patient). All patients had advanced HIV disease; median CD4 = 0.02 x 10(9)/l. Two distinct presentations were seen; 9 patients had a fulminant course as part of a sepsis syndrome, 28 patients had an indolent presentation (18 had a single episode and 10 relapsed on one or more occasions, despite successful treatment of the initial episode). Infection was community acquired in 24 patients. Many patients had risk factors traditionally associated with Ps aeruginosa including neutropenia or indwelling central venous catheters, but 13 had no obvious risk factor. Most patients were receiving systemic pneumocystis prophylaxis and/or broad spectrum antibiotics; 20 had co-existent symptomatic sinus disease. A wide variety of chest radiographic abnormalities were seen including interstitial shadowing, mimicking pneumocystis pneumonia in 12 patients, lobar pneumonia in 2 and bronchial wall thickening in 13 patients. CONCLUSIONS–Ps aeruginosa respiratory infection occurs with increased frequency in patients with advanced HIV disease; in a significant proportion infection is community acquired. Although recognised risk factors were present in two thirds of patients it appears that advanced HIV immunosuppression, use of systemic pneumocystis prophylaxis and/or broad spectrum antibiotics and sinus disease are important risk factors. The diagnosis should be considered in patients with advanced HIV disease who present with new respiratory symptoms.